The Potential of MIPGLE (Microencapsulation of Psidium guajava Leaf Extract) as a Natural Medicine for Tuberculosis - I Putu Anda Tresna Dananta; Putu Prajata Vistara Putera (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2026)
Abstract Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis. Tuberculosis is one of the 10 diseases that cause the largest number of deaths in the world. Therefore, strategic steps to treat Tuberculosis are very necessary. One effort that can be made as an alternative treatment for Tuberculosis patients is the administration of natural medicine. Natural medicines can be produced through the use of natural ingredients such as guava leaves. Guava leaves contain antibacterial compounds, namely chalcone (flavonoid). This research is an experimental study intended to analyze the potential of chalcone in microencapsulation of Psidium guajava leaves extract as a natural medicine for tuberculosis in silico. The research results showed that microencapsulation phytochemistry showed positive results for flavonoid, tannin, phenol and saponin compounds with flavonoid levels of 201.513 mg/100mg QE. The SEM test results show that the Psidium guajava extract has been encapsulated in the maltodextrin-gelatine coating well and has a particle size of 115.442 ?m. This research proven that chalcone has potential as an antibacterial agent through the results of PASS analysis with Pa of 0.284. chalcone with a single dose of drug 1048 mg/kg is known to be feasible as a drug substance with proven feasibility in various pharmaceutical aspects and 4th toxicity shows a low level of toxic impact to the body if this microencapsulation is consumed orally. Keywords: Microencapsulation, Natural Medicine, Psidium guajava, Tuberculosis